The application of fuzzy FMEA and TOPSIS methods in agricultural supply chain risk management (Case Study: Kabupaten Paser) - Ninda Nur Sabila; Anggriani Profita; Yudi Sukmono (Jurnal Teknika, 2022)
The preliminary research stated that there were several mayoral risks that occur in Paser Regency such as, process risks, legal and bureaucracy regulatory risks, demand risks, supply risks, and environmental risk that need to be carried out for further research. This purpose was to analyze the priorities for supply chain activities in XYZ Village, Paser Regency, with the Fuzzy FMEA method using Matlab 2009a software to obtain FRPN values, and carried out mitigation strategies to determine alternative of risk priority for supply chain activities using TOPSIS method to get preference value. The priority risk of the Farmer supply chain was the risk with the F17 code, namely drought which has an impact on land drought with an FRPN value of 749, the Processors supply chain player was the risk with the F30 code, namely Experiencing the destruction of the rice grains during the milling process with an FRPN value of 356, the Distributor supply chain player was a risk with the code F37, namely Uncertainty in the amount of market demand with an FRPN value of 364. The results of the mitigation strategy from the TOPSIS method were for farmers supply chain players, namely Participating in the Rice Farming Business Insurance Program (AUTP) (A1) with first ranking which had a value preference (Vi) of 0.7236, for Processors supply chain players, namely carried out Routine Machine Maintenance (A1) with a first ranking which had a preference value (Vi) of 0.6226, and for Distributor supply chain players, namely doing Forecasting of holes (A3 ) with first rating which had a preference level (Vi) of 0.6425. Penelitian terdahulu menyatakan bahwa terdapat beberapa risiko mayor yang terjadi di Kabupaten Paser seperti risiko proses, risiko regulasi hukum dan birokrasi, risiko permintaan, risiko pasokan, dan risiko lingkungan yang perlu dilakukan penelitian lanjutan. Tujuan penelitian ini ialah untuk menganalisis risiko prioritas pada aktivitas rantai pasok pertanian yang ada di Desa XYZ, Kabupaten Paser, dengan Metode Fuzzy FMEA yang menggunakan bantuan software Matlab 2009a untuk mendapatkan nilai FRPN, dan melakukan strategi mitigasi untuk menentukan alternatif risiko prioritas pada aktivitas rantai pasok pertanian dengan menggunakan Metode TOPSIS untuk mendapatkan nilai preferensi. Risiko prioritas pemain rantai pasok Petani adalah risiko dengan kode F17 yaitu Kemarau yang berdampak pada kekeringan lahan dengan nilai FRPN sebesar 749, pada pemain rantai pasok Penggiling Padi adalah risiko dengan kode F30 yaitu Mengalami kehancuran pada bulir padi saat proses penggilingan dengan nilai FRPN sebesar 356, pada pemain rantai pasok Distributor adalah risiko dengan kode F37 yaitu Ketidakpastian jumlah permintaan pasar dengan nilai FRPN sebesar 364. Hasil strategi mitigasi dari metode TOPSIS adalah pada pemain rantai pasok Petani yaitu Mengikuti Program Asuransi Usaha Tani Padi (AUTP) (A1) dengan peringkat 1 yang memiliki nilai preferensi (Vi) sebesar 0.7236, pada pemain rantai pasok Penggiling Padi yaitu Melakukan Perawatan Mesin Secara Rutin (A1) dengan peringkat 1 yang memiliki nilai preferensi (Vi) sebesar 0.6226, dan pada pemain rantai pasok Distributor yaitu Melakukan peramalan permintaan (A3) dengan peringkat 1 yang memiliki nilai preferensi (Vi) sebesar 0.6425.